ANALYSIS OF AUTOMATIC CONTROL OF THE PROCESS OF UNLOADING AND LOADING TECHNOLOGICAL UNITS OF AGRICULTURAL PURPOSE (Modern information system and technologies, 2018)
The article analyzes prospective microelectronic means of automation of technological processes of unloading and loading of agricultural units, selects a modern element base for the system being designed, considers the structural and principal schemes of a microprocessor system of program control using a programmable microprocessor controller. Keywords: agro-industrial complex, integral microcircuit, microprocessor, control device, software logic controller.